2022
DOI: 10.3389/fneur.2022.973200
|View full text |Cite
|
Sign up to set email alerts
|

One-year recurrence of stroke and death in Lebanese survivors of first-ever stroke: Time-to-Event analysis

Abstract: BackgroundTo date, despite the application of secondary prevention worldwide, first-ever stroke survivors remain at imminent risk of stroke recurrence and death in the short and long term. The present study aimed to assess the cumulative risk rates and identify baseline differences and stroke characteristics of Lebanese survivors.MethodsA prospective longitudinal study was conducted among survivors ≥18 years old who were followed-up for 15 months through a face-to-face interview. Kaplan–Meier method was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 143 publications
0
1
0
Order By: Relevance
“…Of these, nine reported all-cause mortality while one study reported a suicide rate. The studies were from the USA [69,77,78,83,86,89,[92][93][94], England [19,82], Australia [74,88], Denmark [84], Norway [90], Brazil [76], the Netherlands [79], Germany [85], Finland [87], Italy [91], Sweden and Finland [81], Lebanon [95], and South Korea [75,80]. The sample size ranged from 84 to 152,243 participants and the age of the participants ranged from 18 to 74 years.…”
Section: Impact Of Depression On Mortality (N = 24)mentioning
confidence: 99%
“…Of these, nine reported all-cause mortality while one study reported a suicide rate. The studies were from the USA [69,77,78,83,86,89,[92][93][94], England [19,82], Australia [74,88], Denmark [84], Norway [90], Brazil [76], the Netherlands [79], Germany [85], Finland [87], Italy [91], Sweden and Finland [81], Lebanon [95], and South Korea [75,80]. The sample size ranged from 84 to 152,243 participants and the age of the participants ranged from 18 to 74 years.…”
Section: Impact Of Depression On Mortality (N = 24)mentioning
confidence: 99%
“…Patients with recurrent stroke have poor quality of life, high disability rates, and severe cognitive impairment 16 . The risk factors for stroke, recurrence, and mortality not only help medical staff to carry out targeted treatment management strategies but also have important reference value for monitoring disease trends and planning public health interventions 17 . At present, there is a lack of reliable evidence on the independent risk factors for one-year recurrence of and death by IS at home in China to guide patients in choosing appropriate stroke recurrence prevention services.…”
Section: Introductionmentioning
confidence: 99%